2005
DOI: 10.1523/jneurosci.4194-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Four Different Subunits Are Essential for Expressing the Synaptic Glutamate Receptor at Neuromuscular Junctions ofDrosophila

Abstract: Three ionotropic glutamate receptor subunits, designated GluRIIA, GluRIIB, and GluRIII, have been identified at neuromuscular junctions of Drosophila. Whereas GluRIIA and GluRIIB are redundant for viability, it was shown recently that GluRIII is essential for both the synaptic localization of GluRIIA and GluRIIB and the viability of Drosophila. Here we identify a fourth and a fifth subunit expressed in the neuromuscular system, which we name GluRIID and GluRIIE. Both new subunits we show to be necessary for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
234
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(247 citation statements)
references
References 42 publications
7
234
1
4
Order By: Relevance
“…Studies on Drosophila mutants have established that multiple iGluR subunits are required for NMJ function (6,8,9,11). It was previously unclear if this reflects control of receptor assembly, receptor function, cell surface expression, clustering at the NMJ, or a combination of these processes.…”
Section: Efficient Receptor Expression and Function Requires Multiplementioning
confidence: 99%
“…Studies on Drosophila mutants have established that multiple iGluR subunits are required for NMJ function (6,8,9,11). It was previously unclear if this reflects control of receptor assembly, receptor function, cell surface expression, clustering at the NMJ, or a combination of these processes.…”
Section: Efficient Receptor Expression and Function Requires Multiplementioning
confidence: 99%
“…To address the question whether the amount of BRP is increased at individual AZs apposed to the postsynaptic density of GluRIIB animals, we stained NMJs with Nc82 antibodies and simultaneously with antibodies to the postsynaptic GluRIID, an integral component of both IIA and IIB receptors (Qin et al, 2005). The amount of BRP and GluRIID per synapse was quantified by integrating the intensity over the synapse area (Schmid et al, 2008).…”
Section: Quantal Size Is Overestimated By Mepsc Recordingsmentioning
confidence: 99%
“…The Drosophila NMJ is a glutamatergic synapse. Release of glutamate into the synaptic cleft activates ionotropic glutamate receptors (GluRs) permeable to cations (Schuster et al, 1991;Qin et al, 2005). The resulting glutamate-induced depolarization of the muscle membrane also leads to the opening of a variety of voltage-dependent channels (Suzuki and Kano, 1977;Singh and Wu, 1989).…”
Section: Manifestations Of Plasticity At the Larval Neuromuscularmentioning
confidence: 99%
“…The best characterized are the ionotropic DGluRIIA and DGluRIIB subunits that are localized by activity-dependent processes to the postsynaptic densities in the muscle membrane (Broadie and Bate, 1993). Recently it has been shown that other family members, DGluRIII, DGluRIID and DGluRIIE are obligate members of the active DGluRIIA or DGluRIIB containing complexes at the NMJ (Marrus and DiAntonio, 2004;Qin et al, 2005). These receptors are all related to the vertebrate AMPA/Kainate or non-NMDA family of glutamate receptors.…”
Section: Glutamatementioning
confidence: 99%